STEMing Educational Panorama: Architectural Analysis of Style and Structure - Christine Camille Boco; Alyssa Nicole Dela Cruz; Gracie Garing; Glenn Nicole Hinampas; Beyonce Nicole Napoles; Julianne Claire Navarro; Rhea Paragas; Marie Jo Tess Ragos; Cynic Tenedero; Jeft Jerhielle Tulipan; Princess Yvonne Union (Advanced Journal of STEM Education, 2024)
Architectural design is a fundamental intrinsic aspect of human endeavors. This paper aims to provide an analysis of architectural styles and structures at the Technological University of the Philippines—Manila to showcase the different styles and their unique characteristics and how they have shaped the overall visual identity and functionality of the institution.  This study used qualitative analysis anchored by a descriptive method to analyze the style and structures of university landmarks. The researchers studied each photo to determine its architectural style, design elements presented, the arrangement of the structure, materials used, and colors. The findings underscore the need for a comprehensive approach to future development that considers not only visual appeal but also the functionality and adaptability of the structures to promote an enriched educational experience within the Technological University of the Philippines-Manila. Understanding the impact of architectural choices on students and teachers can encourage a broader societal conversation about investing in educational infrastructure that promotes creativity, engagement, and overall well-being. The study concludes that there are various architectural styles used within the buildings of the university; each style has its own visual identity and functionality. This investigation is recommended to extend its relevance to society by emphasizing the role of well-designed campuses in fostering and enhancing educational settings.